2002
DOI: 10.1097/00006454-200203000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Infections diagnosed in the first year after pediatric stem cell transplantation

Abstract: The incidence of infection immediately after transplantation did not differ significantly by type of transplant in this pediatric population. Type of transplant predicted increased incidence of infection 30 days posttransplantation and increased incidence of infection with several organisms traditionally associated with a high mortality rate in the transplant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
101
3
10

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 8 publications
14
101
3
10
Order By: Relevance
“…[1][2][3][4][5][6] We may still have underestimated the true incidence of IFI due to a conservative definition of IFI and the fact that autopsy was not always performed. Interestingly, despite changes in our hospital in prophylactic strategies as of 2008 towards the use of more mould-active antifungal agents, the incidence of IFI did not decrease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5][6] We may still have underestimated the true incidence of IFI due to a conservative definition of IFI and the fact that autopsy was not always performed. Interestingly, despite changes in our hospital in prophylactic strategies as of 2008 towards the use of more mould-active antifungal agents, the incidence of IFI did not decrease.…”
Section: Discussionmentioning
confidence: 99%
“…as used in our institution, was based on available literature [1][2][3][4][5][6] and includes pre-and post-HSCT criteria. For this study, we retrospectively classified all patients into high-or low-risk groups using the same criteria.…”
Section: Patient Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several retrospective pediatric reviews have reported incidence rates of documented IFI ranging from 6 to 12%, with overall mortality rates of 4-14%. [7][8][9] Many patients in need of allogeneic HCT have undergone intensive pre-transplant chemotherapy regimens and have experienced a prior IFI. Although several case series describe the outcome of adults with prior IFI who undergo HCT, [10][11][12][13] there are only sporadic case reports in the pediatric population.…”
mentioning
confidence: 99%